التراث السيناوي كمصدر لاستلهام جداريات فسيفساء معاصرة - محمد، مروة محمود سليمان (الجمعية العربية للحضارة والفنون الإسلامية, 2022)
يعتبر تراث سيناء تراثا له طابع خاص ظهر في عناصر بيئته وأشخاصه وجماليات فنه فكان الفنان متمكن في اختيار خطوطه وأشكاله وألوانه وأبدع فيها، وإذا نظرنا إلى السمات الفنية لهذا التراث، سنجد تنوع وثراء لوني وملمسي غطي على جفاء البيئة السيناوية. ولان التراث يمكنه أن يستمر من خلال التجديد والإضافة ليتماشى مع مسيره الحداثة، فنجد الجداريات وعلى الأخص جداريات الفسيفساء مجالا خصبا لنشر هذا التراث، وذلك من خلال تناوله في علاقات تشكيلية جديدة، تعمل على إخراجه من قالبه التقليدي إلى جانب مختلف من التجديد، ومن خلال أيضا دمجها مع جوانب الحداثة في جداريات الفسيفساء نخرج بجداريات تحمل طابع وجماليات التراث بروح المعاصرة. ومن هنا يسعى هذا البحث إلى كيفية الحفاظ على الاستمرار والانتشار لهذا التراث وتوظيفه في جداريات تتميز بالمعاصرة بشكل يتفق وتصميم جداريات الفسيفساء، التي يمكن عرضها في ميادين وأماكن عامه، تعمل على نشر هذا التراث في بيئات أخرى. لذا يمكن طرح مشكلة البحث في الأسئلة التالية: • إلى أي مدي يمكن توظيف عناصر التراث السيناوي بأسلوب تشكيلي داخل جداريات الفسيفساء؟ • كيف يمكن الدمج بين مظاهر الحداثة في جداريات الفسيفساء والتراث السيناوي للحصول على جداريات معاصره؟ وقد تناول البحث النقاط التالية في الإطار النظري: أ‌- السمات والخصائص العامة لفن الفسيفساء.. ومظاهر الحداثة به. ب‌- عناصر التراث السيناوي.. وأهم سماتها. وفي الإطار التطبيقي اعتمد على تجربه ذاتيه للباحثة قامت من خلالها بتنفيذ مجموعه من التصميمات مستلهمه من عناصر التراث السيناوي، ومتوافقة مع عوامل الحداثة في جداريات الفسيفساء، وتم تحليل تلك التصميمات بشكل افتراضي لما يمكن أن يتم تنفيذه في الواقع. ثم ذكرت الباحثة النتائج التي خلص إليها البحث وتوصياته The Sinai heritage is one of a special nature that appeared in the elements of its environment, people and the esthetics of its art. As the artist was able to choose its lines, forms, colors and innovate in it, and If we look at the artistic features of this heritage, we will find the diversity and richness of color and texture that covered the aridity of the Sinai environment. And because heritage can continue through renewal and addition to keep up with the march of modernity, So we find murals, and especially mosaic murals, a fertile field for the dissemination of this heritage, And that by taking it up in new formative relationships, working to get it out of its traditional form to a different aspect of renewal, through merging them with modernity aspects in the mosaic murals, we create murals bearing the character and aesthetics of heritage in a contemporary spirit. Hence, the research seeks how to preserve the continuity and spread of this heritage and employ it in murals that are characterized by contemporary in a consistent manner with the design of mosaic murals, to be displayed in public squares and places to spread this heritage in other environments. Therefore, the research problem can be posed in the following questions: * To what extent can the elements of the Sinai heritage be employed in a formative manner within mosaic murals? * How is it possible to combine the aspects of modernity in the mosaic murals with the Sinai heritage to obtain contemporary murals? The research deals with the following points in the theoretical framework: A - The general features and characteristics of mosaic art ... and the manifestations of modernity in it. B - The elements of the Sinai heritage ... and its most important features. And In the practical framework It relied on the researcher's own experience through which she implemented a set of designs inspired by the elements of the Sinai heritage, and compatible with modernity factors in mosaic murals, these designs are analyzed by default for what can be implemented in reality. - Then the researcher mentioned the findings and recommendations of the research.
Keywords: الفنون الشعبية -- التراث الفني -- جداريات الفسيفساء -- سيناء -- مصر